Tobacco dependence - Dimitrievska, Deska; Zdraveska, Marija; Todevski, Dejan; Tushevska Mitkovska, Monika (Macedonian Respiratory Society, 2025)
Tobacco is the leading cause of premature death and disability in Europe. Each year, more than 700,000 Europeans die from tobacco-related illness. In Macedonia, 46.6% of the male and 26.8% of the female population are active smokers. These numbers ascertain Macedonia to the high place in Europe by smoking rates. There is nothing more important we can do for patients who smoke than help them stop! Doctors and health professionals must take into account that tobacco dependence is a medical condition and not a habit, vice, pleasure, or life-style choice and it must be diagnosed and treated in the same way as other chronic diseases. Most smokers are not able to stop on their own (without help). Nicotine dependence is a chronic relapsing condition and has two components: physical dependence and psychological dependence. The tenacity of nicotine addiction means that many smokers who attempt to quit will relapse. Relapse is most common within the first few weeks of quitting. The ENSP Tobacco Treatment Guidelines recommend five strategies for addressing tobacco use in clinical settings. Known as the “5As” these strategies are: Ask all patients about smoking status and document in medical record; Advise patients who smoke to quit; Assess readiness to quit; Assist with making a quit attempt, including providing behavioral counselling and prescribing first-line smoking cessation medications; and Arrange follow-up. Behavioral support (Motivational interviewing) is the keystone of tobacco dependence treatment. It is generally matched to the patient’s motivation to quit smoking also known as the patients “stage of change”. There are five stages of change. Pre-contemplation, Contemplation. Preparation, Action and Maintenance. Tobacco dependence may need persistent and repeated therapeutic interventions, as well as long- term follow-up until it is cured. In order to give our contribution to the reduction of tobacco consumption in Macedonia, we are implementing a program for education of doctors and health workers for smoking cessation. The project represents partnership between the Medical faculty in Skopje and the Henry Ford Health System from Detroit, Michigan, USA.
Keywords: tobacco dependence; smoking cessation